The Dynamic Museum and Heritage Futures Workshop: A Handbook for Eco-social Bildung Work in Museums - Paaskoski, Leena; Siivonen, Katriina; Vähäkari, Noora; Latvala-Harvilahti, Pauliina; Pelli, Päivi; Granlund, Maria; Hujala, Teppo (fi=Turun yliopisto|en=University of Turku|, 2025)
By embracing new practices, museums can become even more effective societal actors and contributors to the common sustainability transformation in society. New concepts and methods based on scientific research offer possible development paths for these efforts. The Dynamic Museum is an operating model for museums that invites people to engage in futures processes together and intentionally explore their ideas about the future. The model is built on the foundation of cultural heritage, living heritage, and Heritage Futures. Heritage Futures is a form of heritage that allows individuals to contribute to the cultural sustainability transformation in society. The Heritage Futures Workshop is a tool for futures-oriented thinking that Dynamic Museums can use to create new heritage futures with and for individuals and communities. Taken together, Dynamic Museums, Heritage Futures, and Heritage Futures Workshops allow museums to engage the public in the search for today’s sustainability transformation and understanding the relevance of past transformations. What sets a Heritage Futures Workshop apart is its focus on temporal transitions from the present to the past, from the past to the future, and from the future back to the present. The now-launched Dynamic Museum model, Heritage Futures concept, and five-step Heritage Futures Workshop method (including its preparatory and post-workshop steps) are freely available to all museums. When the materials from a Heritage Futures Workshop are included in a museum’s collections, it opens up the possibility of documenting and examining sustainability themes from different periods of time. The most important tools for museums include reliability, empathy, and long temporal dimensions, as they build mutual understanding and allow for the co-creation of transformative processes. When museums take on an active role in society, they create links with various actors, stakeholders, and communities. Museums can arrange Heritage Futures Workshops in their own exhibition halls or in other spaces, such as outdoors, and they can include multisensory or other artistic exercises. Living heritage work is a key form of activity for any museum, and it is particularly essential for discussing values and working together to find the seeds for everyday sustainability transformations. Ecological reconstruction has become an increasingly pressing issue. New methods are needed to approach to the concept of bildung, stressing the trans-generational and moral understandings that people have about themselves, as a part of the world’s living and non-living nature. Solving the environmental crisis and other futures-oriented work are seen as cultural activities that involve individuals and communities. Merely drawing on previous temporal cultural layers will not result in a sustainability transformation – we need museum activities that combine different temporal levels and provide novel ideas for futures work. The Dynamic Museum aims to do this by incorporating eco-social bildung, a cultural formation that concerns the relationship between living nature and human society, into the already extensive bildung work done by museums. A total of 10 facilitated online and in-person Heritage Futures Workshops were piloted during the DYNAMO project. The project’s pilot partners included the A&DO – Learning Centre for Architecture and Design project, the Finnish Museum of Natural History Luomus, the Finnish Museum of Agriculture Sarka, the Finnish Forest Museum Lusto, the Finnish Museum of Photography, the Museum of Technology, the Museums of Varkaus, and the Finnish Science Centre Heureka. The project also involved extensive and interactive collaboration within the Finnish museum sector. The project placed particular emphasis on disseminating its efforts and results across a multitude of communication channels, such as social media platforms, as communications play a central role in the design of Heritage Futures Workshops.